Control of the Oceanic Heat Content of the Getz‐Dotson Trough, Antarctica, by the Amundsen Sea Low. Issue 8 (18th August 2020) - Dotto, Tiago S.; Naveira Garabato, Alberto C.; Wåhlin, Anna K.; Bacon, Sheldon; Holland, Paul R.; Kimura, Satoshi; Tsamados, Michel; Herraiz‐Borreguero, Laura; Kalén, Ola; Jenkins, Adrian
Abstract: The changing supply of warm Circumpolar Deep Water (CDW) to the West Antarctic continental shelf is responsible for the basal melting and thinning of the West Antarctic ice shelves that has occurred in recent decades. Here we assess the variability in CDW supply, and its drivers, from a multiyear mooring deployed in, and a regional ocean model spanning, the Getz‐Dotson Trough, Amundsen Sea. Between 2010 to 2015, the CDW within the trough underwent a pronounced cooling and freshening, associated with changes in thermohaline properties on isopycnals. Variability in the rate of CDW inflow is controlled by local wind forcing of a shelf break undercurrent, which determines the hydrographic properties of inflowing CDW via tilting of density surfaces above the continental slope. Local wind is coupled to the Amundsen Sea Low (ASL) low‐pressure system, which is modulated by large‐scale climatic modes via atmospheric teleconnections. For the period analyzed, a deeper ASL was associated with westward wind anomaly at the shelf break. Changes in the sea surface slope decelerated the shelf break undercurrent, resulting in less heat accessing the continental shelf and, consequently, a cooling of the Getz‐Dotson Trough. Therefore, the present work suggests that the fate of the West Antarctic ice shelves is closely tied to the future evolution of the ASL. Plain Language Summary: The heat available for the melting of the ice shelves of the Amundsen Sea is supplied by the warm waters flooding the continental shelf. Here we show that the waters flowing into the Getz‐Dotson Trough underwent a pronounced cooling between 2010 and 2015, associated with a weakening of the bottom‐intensified currents within the trough. This process was controlled by changes of shelf break winds. A weakening of the eastward wind impacts the middepth undercurrent system above the continental slope, which controls the inflow of warm water via tilting of density surfaces above the slope. The local winds are modulated by the low‐pressure system located offshore of the Amundsen Sea, known as the Amundsen Sea Low. The Amundsen Sea circulation is controlled by this low‐pressure system, and changes in its configuration can impact the warmer waters flooding the West Antarctic continental shelf, with consequences for the melting of the region's ice shelves. Key Points: Circumpolar Deep Water inflow to the Getz‐Dotson Trough, Amundsen Sea, is investigated with a multiyear mooring On‐shelf heat content decreased between 2010 and 2015 in response to weaker Circumpolar Deep Water inflow Getz‐Dotson Trough cooling is driven by a westward wind anomaly at the shelf break, associated with a deeper Amundsen Sea Low